ADMINISTRATIVE AND LEGAL INSTRUMENTS FOR PROVIDING QUARANTINE AND ANTI-EPIDEMIC MEASURES (Bulletin of criminological association of Ukraine, 2024)
It was found that administrative and legal instruments are a collective category that expresses actions, operations and processes used by state authorities and local self-government bodies to perform the public and legal functions assigned to them. The use of a particular instrument is strictly individualized, as it is directly related to the competence and powers of a specific subject of administrative legal relations. That is why it is emphasized that it is impossible to determine the general composition of this category, although its basic features are generally sufficient to establish the specifics of the manifestation within the framework of individual public and legal branches. It is proven that administrative and legal instruments for ensuring quarantine and anti-epidemic measures are a set of legally significant actions, operations and processes regulated by the legislation of Ukraine and carried out in accordance with the established procedure by authorized entities, which are used to create the necessary conditions (legal, economic, managerial, etc.) and organize the implementation of quarantine and anti-epidemic measures on the territory of Ukraine.
Keywords: quarantine; epidemic; anti-epidemic measures; administrative and legal instruments; provision; quarantine measures